2016
DOI: 10.1038/srep34916
|View full text |Cite
|
Sign up to set email alerts
|

Multiple discrete soluble aggregates influence polyglutamine toxicity in a Huntington’s disease model system

Abstract: Huntington’s disease (HD) results from expansions of polyglutamine stretches (polyQ) in the huntingtin protein (Htt) that promote protein aggregation, neurodegeneration, and death. Since the diversity and sizes of the soluble Htt-polyQ aggregates that have been linked to cytotoxicity are unknown, we investigated soluble Htt-polyQ aggregates using analytical ultracentrifugation. Soon after induction in a yeast HD model system, non-toxic Htt-25Q and cytotoxic Htt-103Q both formed soluble aggregates 29S to 200S i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 48 publications
1
27
0
Order By: Relevance
“…This argues for the concept that – if aggregation promotes toxicity – it is not by aggregation per se , but rather via a distinct population of aggregates. In this study, the authors argued for a correlation of mid-sized aggregates with cytotoxicity and could show that factors blocking toxicity of Htt103Q [including elimination of the poly(P) region] also changed the aggregation pattern, including a decrease of mid-sized and large aggregate populations ( Xi et al, 2016 ). A large body of evidence indicates that Hsp40 chaperones can suppress poly(Q) aggregation, an observation already made as early as 2000 from yeast studies ( Muchowski et al, 2000 ).…”
Section: Cytotoxic Mechanisms In Hd Yeast Modelsmentioning
confidence: 82%
See 1 more Smart Citation
“…This argues for the concept that – if aggregation promotes toxicity – it is not by aggregation per se , but rather via a distinct population of aggregates. In this study, the authors argued for a correlation of mid-sized aggregates with cytotoxicity and could show that factors blocking toxicity of Htt103Q [including elimination of the poly(P) region] also changed the aggregation pattern, including a decrease of mid-sized and large aggregate populations ( Xi et al, 2016 ). A large body of evidence indicates that Hsp40 chaperones can suppress poly(Q) aggregation, an observation already made as early as 2000 from yeast studies ( Muchowski et al, 2000 ).…”
Section: Cytotoxic Mechanisms In Hd Yeast Modelsmentioning
confidence: 82%
“…Interestingly, a recent study in yeast has shown different stages of aggregation for both Htt25Q and Htt103Q with significant alterations over time, including the surprising finding that (non-toxic) Htt25Q can form large aggregates as well ( Xi et al, 2016 ). This argues for the concept that – if aggregation promotes toxicity – it is not by aggregation per se , but rather via a distinct population of aggregates.…”
Section: Cytotoxic Mechanisms In Hd Yeast Modelsmentioning
confidence: 99%
“…In the D. melanogaster samples (Figure 3A), while two major pools of aggregation are quantified here (1–20 and 20–20000 S), recent SV analysis of Htt aggregation in yeast suggests a total of four distinct aggregate pools might be defined on the basis of differential behavior. In yeast, Xi et al 21 show evidence for two differently behaving pools in the range of 20–80 S and above 100 S. They noted a stronger correlation between the level of aggregation and toxicity for the smaller range than for the >100 S range. Thus, the other two pools that we note in our work would encompass the 1–20 S range and a range of >500 S, outside the window of observation of Xi et al While these pools are empirically defined, they are reproducible, with slight collective x -axis shifts of the pools because of uncertainty in the position of the sample meniscus (compare Figure 3 with the distributions from separate experiments shown in Figure 7).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, with 40 or more polyQ repeats, HD emerges with 100% penetrance (Sarkar et al, 2007). Furthermore, the midsized aggregates (33S to 84S) are more stable and correlative with toxicity, which indicates that the mid-sized aggregates, such as 33S to 84S, are optimal choices used for the study (Xi et al, 2016). Therefore, HTT74 was widely used to established the HD cellular model (Ravikumar et al, 2004;Sarkar et al, 2007;Wyant et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the HD knock-in mice also expressed full-length mHtt (Zhao et al, 2016). Emerging evidence has shown that the mHtt aggregates induce cytotoxicity, which is closely related to neuronal death in HD (Lu and Palacino, 2013;Xi et al, 2016), and the reduction in mHtt aggregates has been proven to rescue HD-related phenotypes through genetic and chemical modifications (Jimenez-Sanchez et al, 2015;Yu et al, 2017). Therefore, the clearance of mHtt has become a promising strategy for HD therapy.…”
Section: Introductionmentioning
confidence: 99%